Development of a critical heat flux correlation based on a mechanistic model under subcooled flow boiling conditions. Issue 3 (4th March 2023) - Yodo, Tadakatsu; Odaira, Naoya; Ito, Kei; Ito, Daisuke; Saito, Yasushi
ABSTRACT: In this study, a mechanistic model-based correlation for the critical heat flux is proposed to meet the practical requirements for the design and safety analysis of pressurized water reactors. The correlation is based on a liquid sublayer dryout model for a single tube, which includes physical parameters, such as sublayer thickness and vapor blanket velocity, expressed as an explicit nondimensional equation and modified using a look-up table for critical heat flux to ensure a wide applicable range of coolant conditions. The correlation predicts a critical heat flux for the subcooled region in the pressure range of 0.1–18 MPa, mass velocity range of 500–8000 kg/m 2 s, and a thermal equilibrium quality ranging from −0.5 to −0.05 with high accuracy of the departure from nucleate boiling ratio limit based on a 95% probability and a 95% confidence of 1.20. GRAPHICAL ABSTRACT: uf0001